Features of the Course of PsychoOrganic Disorders in Diabetes Mellitus - Mardiyev Otabek Asliddinovich; Rajabov Hikmat Toshevich (Genius Journals, 2023)
diabetes mellitus differs from most endocrine diseases by dividing the psychopathological picture of the disease into two large periods: the onset of the disease and the period of complications. With the development of encephalopathic changes, signs of psychoendocrine syndrome appear and its rapid progression with the formation of a psycho-organic syndrome can be observed. The high prevalence, chronic course of the disease, multifactorial etiology, variety of somatic, neurological and mental manifestations make diabetes mellitus an optimal model for studying and systematizing mental disorders in patients with a somatic profile and developing technologies for their diagnosis and treatment.
Keywords: psycho-organic disorders; diabetes mellitus; encephalopathy; cognitive dysfunctions